Zasada zachowania integralności prawa do obrony. Analiza przypadków - Czujek, Marcin (Ius Matrimoniale, 2018)
Right of defense, being the actual possibility of intervening the parties is one of the essential elements of the structure of a just process. Preservation of the integrity of this law depends not only on the parties themselves, who are allowed to take any attitude towards their rights, but also, and perhaps above all, this task is for a judge whose goal, in addition to the search for truth is also the concern for the true contradictoriality of the process. The decisions and instances of violation of the integrity of the right to defense discussed in the article, indicate how important is this role in canonical process of the nullity of marriage.